Mobile application prototyping using Artificial Intelligence to support childhood tuberculosis diagnosis - Katerine Souza Picoli; Flávia Regina Souza Ramos; Denise Maria Guerreiro Vieira da Silva; Bruno da Veiga Thurner; Daniel Souza Sacramento; Irineide Assumpção Antunes; Lucas Lorran Costa de Andrade; Amélia Nunes Sicsú (Revista Brasileira de Enfermagem, 2025)
ABSTRACT Objectives: to develop a mobile application prototype using Artificial Intelligence (AI) to predict and support the diagnosis of pulmonary tuberculosis in children – TB Kids. Methods: technological development research of the prototyping type, based on the Rational Unified Process model and its four stages: conception, elaboration, construction and transition. The development of the TB Kids prototype took place from November 2022 to July 2023. Results: the TB Kids prototype has features for risk assessment, nutritional assessment, tuberculin skin test, investigation of antibiotic therapy and contacts, interpretation of chest X-rays through AI with risk graph and decision-making, complementary guidance and recording of the clinical picture. Conclusions: the high-fidelity mobile application prototype has a consistent interface, responding with creativity and innovation to Sustainable Development Goal 3 and the lack of prediction software using AI in the diagnosis of children at risk for tuberculosis.